Synthetic Integrin-Targeting Dextran-Fc Hybrids Efficiently Inhibit Tumor Proliferation In Vitro - Schneider, Hendrik; Englert, Simon; Macarrón Palacios, Arturo; Lerma Romero, Jorge Alberto; Ali, Ataurehman; Avrutina, Olga; Kolmar, Harald (Frontiers in Chemistry, 2021)
Herein, we present the design, synthesis and biological evaluation of novel integrin-targeting molecular hybrids combining RGD peptides and a potent cytotoxin presented on dextran polysaccharide. Based on an aglycosylated Fc as centerpiece, endosomal-cleavable cytotoxic agent monomethyl auristatin E (MMAE) and dextran as multimerization site were covalently connected by two bioorthogonal enzyme-mediated reactions site-specifically. Decoration of dextran with cyclic RGD peptides, introduced by copper “click” reaction, resulted in the final constructs with the potential to kill integrin-overexpressing tumor cells. We found that these modifications had little impact on the stability of Fc scaffold and the RGD-bearing construct showed good binding properties of αvβ3 expressing U87MG cells. Furthermore, the construct showed remarkable anti-proliferative activity. These results demonstrate the general capability of our design to provoke receptor-mediated endocytosis upon binding to the cellular surface, followed by endosomal cleavage of the linkage between Fc-dextran and MMAE and its subsequent release. Our approach opens new avenues to transcribe small molecule-binders into tailor-made multimeric molecular hybrids with antitumor potential.